High serum concentration of L-kynurenine predicts unfavorable outcomes in patients with acute myeloid leukemia. Issue 1 (2nd January 2016) - Mabuchi, Ryoko; Hara, Takeshi; Matsumoto, Takuro; Shibata, Yuhei; Nakamura, Nobuhiko; Nakamura, Hiroshi; Kitagawa, Junichi; Kanemura, Nobuhiro; Goto, Naoe; Shimizu, Masahito; Ito, Hiroyasu; Yamamoto, Yasuko; et al.
Abstract : The immunomodulatory effects of indoleamine 2, 3-dioxygenase (IDO) are ascribed to its ability to catalyze the breakdown of the L-tryptophan along the L-kynurenine pathway. Because blasts from patients with acute myeloid leukemia (AML) express IDO, the goal of this study was to investigate the role of L-kynurenine as a prognostic marker for AML. We enrolled 48 AML patients. L-kynurenine concentrations were measured by high-performance liquid chromatography. The median serum L-kynurenine level was 1.67 μM. There was no significant difference in the complete remission rate between patients with L-kynurenine < 2.4 (77%) and ≥ 2.4 μM (75%). However, 3-year overall survival (OS) rates were significantly better in patients with low L-kynurenine levels (76%) than in those with high L-kynurenine levels (11%) ( p < 0.0001). Furthermore, in intermediate-risk cytogenetics patients, only L-kynurenine was significantly associated with OS ( p < 0.005). Multivariate analyses revealed that L-kynurenine and high leukocyte count were independent prognostic factors.